Patient management for cochlear implant recipients in audiology departments: A practice review. (3rd May 2016) - Lorens, Artur; Skarzynski, Henryk; Rivas, Adriana; Rivas, José Antonio; Zimmermann, Kim; Parnes, Lorne; Lassaletta, Luis; Gavilán, Javiér; Bodt, Marc De; van de Heyning, Paul; Martin, Jane; Raine, Christopher H.; et al.
Abstract : Objectives : To determine and evaluate the time clinics needed to complete the sub-processes involved in the first-fitting and follow-up fitting of people with a cochlear implant. Methods : Eight HEARRING clinics completed a questionnaire recording how long it took to complete the sub-processes involved in first-fitting and follow-up fitting cochlear implant recipients. The mean times of clinics and procedures were then compared. Results : Questionnaires on 77 patients were completed. Clinics varied widely on time spent on each sub-process in both first- and follow-up fittings. Total first-fitting times were similar across clinics. Follow-up fitting times varied more across clinics although this may have been due to differences in questionnaire interpretation. Discussion : If a patient management plan can help increasingly busy cochlear implant clinics provide high-quality care more efficiently, essential first steps are determining which procedures are generally performed and how long their performance takes. Until reliable data are gathered, constructing a patient management plan or reaping the potential benefits of its use will remain elusive; clinics will have to find what solutions they can to meet rising workload demands. Conclusion : The variation in time spent on each sub-process may suggest that some clinics have more efficient workflow procedures. Compiling a best practice for each process could be instrumental in creating a professional process management plan that would increase efficiency without sacrificing quality of care.